The Correlation Between Cervical Provocation Tests and Compression Severity in EMG Findings of Cervical Root Syndrome Patients - Farah Shabri Alifia Zahra; Shahdevi Nandar Kurniawan; Alfred Julius Petrarizky (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Background: Medical professionals are often found using cervical provocation tests and Electromyography (EMG) examination to diagnose Cervical Root Syndrome (CRS). Although EMG examinations are unavailable in primary health care facilities due to the lack of equipment, the results of cervical provocation tests are expected to correlate with the findings of the EMG examination. Objective: This study aimed to investigate the correlation between cervical provocation tests (Lhermitte and Spurling) and compression severity of CRS. Methods: 85 medical records that met the inclusion and exclusion criteria were selected using a stratified random sampling method. Subsequently, cervical provocation tests were scaled ordinal, stratified into negative, positive 1, and positive 2, while compression severity was grouped into mild, moderate, and severe. The data obtained was analyzed using SPSS, and correlation analysis was conducted using the Spearman method. Results: The result showed that cervical provocation tests had a very weak negative correlation with the CRS compression severity, and the values obtained were not statistically significant (R = -0.105 and p = 0.341). Conclusion: The results showed that there was no significant correlation between cervical provocation tests and CRS compression severity. Therefore, cervical provocation tests cannot be depended on as a representation of CRS compression severity.